Implications of Non-Payment During Contract Execution in Public Procurement in Peru - Sánchez, José Antonio (2025)
One of the problems that arises in contracting with the state is the payment of compensation when there is conformity of the goods, services in general, and consultancies. Even though the contractors have the respective compliance, the state entities do not comply with the payment or do so in a deferred manner, greatly harming the contractor, because despite having complied with the obligations under their charge, they do not receive the agreed consideration, even having to go to a means of dispute resolution such as the arbitrator, in order to achieve payment.This lack of payment, or late payment, is not effectively sanctioned in Peru, and may generate acts of corruption or greater expenses for the contractor so that the entities comply with the obligations under their responsibility.In light of the above, it is proposed that public servants in charge of purchasing, logistics, or payment be appointed by SERVIR; that disciplinary action for failure to make timely payments be sanctioned by the Comptroller General of the Republic; that entities provide contractors with guarantees for timely payment; and, finally, for certain goods, entities may make payment upon delivery.